The Effect of Work-Life Balance, Work Environment and Work Stress on Employee Performance of PT Coalindo Adhi Perkasa with Organizational Citizenship Behavior as an Intervening Variable - Nanda, Resty Meilia; Iskandar, Rusdiah; Yudhyani, Eka (Jurnal Ilmiah Sumber Daya Manusia, 2025)
PT Coalindo Adhi Perkasa is a mining contractor company that implements a roster work system, in which employees work for a certain period and reside in company-provided housing. This work pattern has the potential to affect employees' work-life balance, working conditions, and stress levels, which ultimately impact their performance. This study aims to analyze the influence of work-life balance, work environment, and job stress on employee performance, with organizational citizenship behaviour (OCB) as an intervening variable. The research employed a quantitative approach using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with the SmartPLS 4 software. The sample was determined through purposive sampling based on the criteria of employees working under the roster system, living in company housing, and not commuting daily. From a total population of 163 employees, 44 respondents met the criteria. Data were collected using a questionnaire with a five-point Likert scale. The findings indicate that work-life balance has a positive but insignificant effect on OCB and employee performance. The work environment has a positive and significant effect on both OCB and performance. Conversely, job stress has a negative but insignificant effect on OCB and performance. OCB has a significant positive effect on employee performance and partially mediates the relationship between the work environment and performance, but does not mediate the effects of work-life balance or job stress. The implications of this study emphasize the importance of creating a supportive work environment and strengthening OCB as strategies to improve performance in the mining sector, while personal factors such as work-life balance and job stress should be managed through organizational support to prevent a decline in employee commitment.